Factors Engaging College Students in Online Learning: An Investigation of Learning Stickiness - Aixia Li (SAGE Publishing, 2021)
This study extended the Expectancy Confirmation model (ECM) to examine the factors that influence online learning stickiness. The structural equation modeling was used to reveal the relationships among the factors through a survey of 395 online consumers. The findings indicate that learning stickiness was significantly impacted by switching cost and satisfaction. Learners’ perceived usefulness, perceived interactivity, and expectation confirmation have a significant effect on their satisfaction. Furthermore, learners’ perceived usefulness was significantly influenced by their perceived interactivity and expectation confirmation. The results of this research also provide sustainable development directions for online platforms, such as the quality of curriculum design and the level of interaction between curriculum platforms.